Effectiveness of Solifenacin versus Mirabegron in the Treatment of Overactive Bladder: A Prospective Cohort Study - Shyamali Dutta; Korlapally Divya Bhavani; Avik Das; Debadrita Das; Palash Mazumder (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Overactive Bladder (OAB) syndrome is a symptom-complex defined as urinary urgency, usually accompanied by increased daytime frequency and nocturia, with or without urgency incontinence, in the absence of urinary tract infection or other obvious pathology. Aim: To compare the efficacy and safety between Solifenacin and Mirabegron in treatment of OAB. Materials and Methods: A prospective cohort study was conducted in the Department of Obstetrics and Gynaecology at Medical College, Kolkata, West Bengal, India from May 2020 to April 2021. The study was conducted on 110 willing patients divided into two groups, with Solifenacin 5 mg given to Group-1 and Mirabegron 50 mg given to Group-2, respectively. The sampling frame was women of age > 40 years visiting the hospital’s urogynaecology clinic. Study variables were age, the difference between baseline and post-treatment number of urination episodes in 24 hours and at night, urgency, leakage episodes and side-effects experienced in each group. Mann-Whitney U Test was used for comparison between two groups while Chi-square test was used for side-effect comparison. Results: The mean age of the study population was approximately 61.41 years. After nine weeks of treatment, the reduction in total number of urinations in 24 hours was 54.17% in Group-1 and 9.71% in Group-2, which is statistically significant, reduction in the number of urination at night was 79.53% and 76.79%, the reduction in number of leakage episodes was 78.19% and 75.49%, reduction in urgency episodes was 76.96% and 75%, frequent adverse effects were constipation (43.64% vs 7.27%) and dry mouth (56.36% vs 9.09%). Conclusion: The study showed that both drugs are effective in reducing OAB symptoms. Regarding adverse effects, dry mouth was more common with Solifenacin.